2010
DOI: 10.1159/000279621
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Public Engagement for Effective Input in Policy Development on Human Tissue Biobanking

Abstract: We begin with the premise that human tissue biobanking is associated with ethical ambiguities and regulatory uncertainty, and that public engagement is at least one important element in addressing such challenges. One is then confronted with how to achieve public engagement that is both meaningful and effective. In particular, how can public engagement on the topic of biobanking be implemented so that (a) it is perceived broadly as legitimate and (b) the results of the engagement are relevant and useful to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 62 publications
2
79
0
Order By: Relevance
“…This study also provides evidence of the public's ability to form coherent judgments and expectations about a new or future policy issue using structured, facilitated deliberative discussion that took place among a small group of citizens over several hours using recognized methods. [22][23][24][25] Although not intended to represent the views of the general population, the findings contribute novel and timely insights into the perceptions, values and concerns that a group of citizens and potential users hold toward personalized medicine. Importantly, the citizens' panel was concerned that personalized genomic tests might be used to ration care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also provides evidence of the public's ability to form coherent judgments and expectations about a new or future policy issue using structured, facilitated deliberative discussion that took place among a small group of citizens over several hours using recognized methods. [22][23][24][25] Although not intended to represent the views of the general population, the findings contribute novel and timely insights into the perceptions, values and concerns that a group of citizens and potential users hold toward personalized medicine. Importantly, the citizens' panel was concerned that personalized genomic tests might be used to ration care.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these represent validated methods of deliberative processes, 21 which previous studies have shown to elicit in-depth views, emphasizing informed, values-based reasoning, with the goal of reaching common ground on complex, value-laden topics. [22][23][24][25][26] These deliberative methods are increasingly used to elicit public values on genomics policy issues. 17,24,25,27 The focus of this paper is on the panel's review and deliberations of GEP for early stage breast cancer, and the general topic of personalized medicine.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, racial/ethnic minorities are already underrepresented in clinical trials (Chen et al 2014;Anderson 2004;Bruner et al 2006;Murthy et al 2004) that have been the principal conduits to cancer drug development, and unless these trends are reversed, health disparities will be even more magnified as treatments using personalized medicine technologies increase (Hall and Olopade 2006;Rebbeck et al 2006). To address these needs, institutions with biobank repositories have conducted deliberative engagement with participants to increase the community's knowledge of biobanking and inform institutional policies Lemke et al 2012;O'Doherty and Hawkins 2010). The findings from these studies suggest that such practices increase public support for biobanking, engender trust among participants, and translate public input into policy (O'Doherty et al 2012;Streicher et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Robust public engagement becomes akin to a surrogacy-advance directive conversation in responsible biobanking. [13][14][15] (Although some biobanks already conduct admirable community engagement processes, the surrogacy model articulates the underlying rationale that is obscured by the consent model. It is not clear why community engagement would be necessary if individual informed consent to donate were coherent.…”
Section: From Consent To Surrogacymentioning
confidence: 99%